Technological resources in language learning for Virtual Environments - Juárez Velásquez, Mario Orlando; Rosales Henríquez, Débora Ester; Sibrian Ortiz, Josue Adalberto (2024)
In these times, the use of technological tools has become more and more popular at the time of teaching and learning a foreign language. In all these interaction with new ways of teaching and learning, the internet is becoming probably the most used and reliable tool that offers an almost unlimited source of resources to improve the second language acquisition. Therefore, the main purpose of this report is to present all about the course called Administration of Virtual Environments for the Teaching and Learning of the Foreign Language, taught to the students of the Bachelor's Degree in English Language of the Faculty of Sciences and Humanities of the University of El Salvador, with the objective of offering students the fundamentals of online education and its application in the teaching of the English language, the theoretical foundations, the use of technological tools and to use at least four web tools for the design of educational materials. So they can teach their quality virtual classes, due to the global health problem caused by COVID-19.